CALCULATION OF VOLUMETERIC AND THERMODYNAMIC PROPERTIES FOR PURE HYDROCARBONS AND THEIR MIXTURES USING CUBIC EQUATIONS OF STATE - Sameera M. Hamad-Allah; Munqith N. Reshag (Journal of Engineering, 2010)
The objective of this study was to develop a complete package for prediction of volumetric and thermodynamic properties of pure hydrocarbons fluids and their mixtures in one and two phase regions. Two cubic equations of state that are Peng-Robinson and Soave-Redlich-Kwong were used with volatile and black oils respectively to calculate the desired properties in addition to bubble point and dew point pressures and temperatures. Different values of binary interaction parameter were used for each equation and effects of this parameter values on the prediction are examined. Also values of this parameter between the plus-fraction and other component have been evaluated for first time. In calculation of heat capacity, four different mixing rules have been proposed to evaluate the temperature derivatives in case of the mixtures. Wide comparisons with the literature experimental data were made which indicated that both equations of state predict accurately different properties and marked improvements are achieved by use binary interaction parameter other than zero. Also both equations predict bubble point pressure of a certain mixture approximately with same accuracies using the recommended values of binary interaction parameter. Among the proposed mixing rules, Kay’s one appeared the best one to determine temperature derivatives.